The relationship between serum level of fibroblast growth factor 23 and valvular calcification in chronic kidney disease patients - XU Feng-bo; LIU Hui-lan; SUN Yi; LI Guo-gang; ZHU Ying-hui (Linchuang shenzangbing zazhi)
Objective To determine the serum level of fibroblast growth factor 23（PGF23） in chronic kidney disease（CKD） patients and explore the relationship between FGF23 and valvular calcificatioa Methods eighty-nine CKD patients and twenty-eight people（control group） whose renal functions were normal were enrolled in this study.The patients in CKD were divided into CKD 1-2 group（16 patients）,CKD 3-4 group（20 patients）,CKD 5 group（16 patients） and CKD 5D（37 patients）.Phosphate,calcium,triacylglycerol,total cholesterol.Low density lipoprotein cholesterol high density lipoprotein cholesterol,parathyroid hormone and FGF23 in their serum were determined.The level of FGF23 in serum were detected by the method of ELISA.All the peoples were divided to VC group and non-VC group according to echocardiogram.Results（1）The Log iPTH,Log FGF23 and valvular calcification in CKD 5D group was much higher than other groups.（2）The Log FGF23 and Dialysis proportion in VC group was much higher than non-VC group.（3） Logistic regression analysis revealed that the level of Log FGF23,age,Hypercholesterolemia and history of diabetes mellitus was the influencing factor of CKD patients.Conclusions The serum level of FGF23 in CKD patients is higher.With the worsening of renal function,FGF23 increased,and the elevation of FGF23 is relative to the valvular calcificatioa